(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Trends of distribution and dispersal of alien species of the Artemisia vulgaris L. aggregate (Asteraceae) in Ukraine are discussed. New localities of A. verlotiorum Lamotte in Crimea (Nikita, Gurzuf) are reported. Previously this alien species was known from the Nikita Botanical Garden, but recent herbarium collections from Crimea were lacking. Thus, the occurrence of A. verlotiorum in the Crimea is reconfirmed. New finds of alien species of Artemisia sect. Artemisia in Ukraine are expected and thus Ukrainian botanists should pay more attention to that group. Some aspects of taxonomy and geography of the group are considered.